Implementing Good Corporate Governance in Indonesia: A Strategic Approach - Wahyudi Wibowo; Hananiel M. Gunawan (Journal of Accounting, Business and Management (JABM), 2015)
Good Corporate Governance (GCG) has been widely acknowledged as the global best standard of corporate governance practices. Indonesian business society has been started to implement the standard since 2001. But many corporations currently still struggle to find their best model on GCG implementation. This study is based on a field research at ASGR, a public listed IT company in Indonesia which had passed valuable experience in implementing GCG principles. This study primarily used the company's data from the period of 2000 to 2001, which was the period for ASGR to do early studies and preparations to implement GCG. This paper recommends a strategic model for the implementation of GCG in Indonesia. The model uses a system approach as the analytical basis to connect the implementation of GCG with the strategic context of the company. It includes the utilization of multi-stakeholder, strategic responses, and global benchmarking analysis as the useful tool to guide the strategic implementation of GCG.